2022
DOI: 10.1200/jco.2022.40.16_suppl.e15001
|View full text |Cite
|
Sign up to set email alerts
|

Ocular toxicities associated with anticancer therapies: Are we missing something in the blind spot?

Abstract: e15001 Background: Ocular toxicities are common challenges associated with anticancer agents, including small molecules, antibody-drug conjugates (ADC), targeted antibodies, particularly those targeting Epidermal Growth Factor Receptor (EGFR), Mitogen-activated protein kinase (MEK) and cytotoxic T-lymphocyte-associated protein 4 (CTLA4). This subject suffers from a paucity of consensus guidelines, especially drug class versus severity of toxicity versus ocular anatomy. The aim of this paper is to examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The retinal layer thickness ratio remained unchanged, and no significant amplitude differences were observed between the ADC and control groups in the ERG and OptoMotry tests. However, some studies have reported ocular toxicity results associated with ADCs [ 127 , 128 , 129 , 130 ]. Although the exact mechanisms underlying the ocular toxicity of ADCs remain unclear, increased adverse reactions have been observed, particularly with maytansinoid- and MMAF-containing ADCs [ 130 ].…”
Section: Recent Progress and Challenges In Overcoming Biological Barr...mentioning
confidence: 99%
“…The retinal layer thickness ratio remained unchanged, and no significant amplitude differences were observed between the ADC and control groups in the ERG and OptoMotry tests. However, some studies have reported ocular toxicity results associated with ADCs [ 127 , 128 , 129 , 130 ]. Although the exact mechanisms underlying the ocular toxicity of ADCs remain unclear, increased adverse reactions have been observed, particularly with maytansinoid- and MMAF-containing ADCs [ 130 ].…”
Section: Recent Progress and Challenges In Overcoming Biological Barr...mentioning
confidence: 99%